Деякі аспекти по визначенню впливу складових сили тертя на процес різання при глибокому свердленні алюмініїв - Маршуба, В'ячеслав Павлович; Плахотнікова, Інна Борисівна (Українська інженерно-педагогічна академія, 2015)
Обґрунтування експериментальних залежностей по визначенню в силі тертя, адгезійної і механічної складової, при взаємодії швидкорізальної сталі та ливарних алюмінієвих сплавів в умовах дії високого контактного тиску і великих температур по контактним ювенальним поверхням. Експеримент проводився по визначення частки адгезійної взаємодії в силі різання при обробці ливарних алюмінієв. Для досягнення поставленої мети по встановленню кількісних залежностей адгезійної і механічної складової в силі тертя. Показана методика направлення досліджень по оптимізації процесів різання матеріалів.

Ground of experimental dependences on determination in force of friction, adhesive and mechanical constituent, at co-operation of high-speed steel Р6М5Ф3 and casting aluminum alloys in the conditions of action of pinholes deep boring and high contact pressure and large temperatures on contact surfaces. The experiment was conducted on determination of particle of adhesive and mechanical co-operation in force of cutting at treatment of deep holes and in castings from aluminum alloys. For achievement of the put purpose on establishment of quantitative dependences of adhesive and mechanical constituent in force of friction the different methodologies for estimation the experimental data received in conditions of the cutting process modeling are used. The method of direction of researches on optimization of processes of cutting of materials is shown.
Some facets of the estimation of the friction force components influence on the cutting process by deep boring of aluminum
Keywords: свердла гвинтові; верстат агрегатний; лінії автоматичні; середовище технологічне; середовище змащувально-охолоджувальне; зв'язок адгезійний